Transmission profiling of phase shifted 1D Bragg reflectors in standard and coaxial waveguide - MacInnes, P; Konoplev, I; Cross, A; Phelps, A; Ronald, K; IEEE (2007)
A Bragg reflector can be defined as a region which shows a periodic change in the wave impedance, leading to gaps in the transmission pass-band. We report the results of initial experimental and theoretical work into the control of the transmission profiles of 1D Bragg reflectors, realized through the introduction of a ±π phase shift defect in the 1D corrugation.